Evaluasi Sistem Hukum Perbankan Syariah Pasca Undang-Undang No. 21 Tahun 2008: Systematic Literature Review - Febriza, Milla (TAWAZUN: Journal of Sharia Economic Law, 2025)
Sharia banking in Indonesia has shown rapid growth over time, in line with the issuance of various regulations that specifically govern the activities and operations of sharia financial institutions. This study aims to examine and analyze the legal system governing sharia banking after the enactment of Law No. 21 of 2008. This research is a qualitative Systematic Literature Review (SLR) using the Prisma model. The data sources in this study were obtained from publications found through Google Scholar from 2008 to 2024. The data collection technique in this study used Publish or Perish software. The data analysis technique used the Prisma model presented in a flow diagram. The results of the study indicate that based on previous studies related to the Islamic banking legal system after the issuance of Law No. 21 of 2008 concerning Islamic Banking by the government, it was found that the existence of Islamic banking has experienced significant development. With this Law, the existence of Islamic banking has legal regulations that serve as the main legal basis for Islamic banking. This Law also provides legal certainty regarding operational aspects, dispute resolution, and contract principles in accordance with the maqashid syariah in Islamic banking.